PENINGKATAN PEMAHAMAN PERSONALIA PT. ASIA FORESTAMA RAYA PEKANBARU: PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL - Zulkarnaen Noerdin; Robert Libra; Rizana (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2019)
The need for understanding the existence of Industrial Relations Dispute Resolution (PPHI) based on Law Number 2 of 2004 concerning PPHI is very urgent in the company. There are a lot of workers and company personnel who do not / do not know about the existence of this regulation, if there are problems in the industrial field, the workers do not know the existing regulations, including understanding so that no disputes occur The solutions offered by the team are lectures, dialogues and discussions to solve the problems faced. The work procedures to support the methods offered are lectures held 1 (one) hour, and dialogues and discussions for 2 hours or according to the needs of partners as long as they are within the period of implementation of this program. The participation of partners in the community service program is to provide the place and time for program implementation and to present partner members as audiences. The output that will be produced according to the plan of community service activities is: for partners, of course, increased understanding of the Industrial Relations Dispute Settlement (PPHI) based on Law Number 2 of 2004 concerning PPHI. For the outcome proposals to be achieved are scientific articles and cannot be separated from the Tri Darma of Higher Education